Psychological Distress and Suicidal Ideation in Patients With Atrial Fibrillation: Prevalence and Response to Management Strategy. Issue 18 (18th September 2018) - Walters, Tomos E.; Wick, Kate; Tan, Gabriel; Mearns, Megan; Joseph, Stephen A.; Morton, Joseph B.; Sanders, Prashanthan; Bryant, Christina; Kistler, Peter M.; Kalman, Jonathan M.
Abstract : Background: An association between atrial fibrillation (AF), anxiety, and depression is recognized, but the spectrum of psychological distress remains unclear. We aimed to characterize the severity and predictors of distress associated with AF in a tertiary population and its response to AF management. Methods and Results: Seventy‐eight patients with symptomatic AF underwent evaluation, including of AF symptom severity, health‐related quality of life, psychological distress, suicidal ideation, and specific personality traits. Twenty participants underwent AF ablation and 58 were managed medically, with repeat assessments at 4, 8, and 12 months. Severe distress (Hospital Anxiety and Depression Scale score, ≥15/42) was identified in 27 of 78 (35%). Independent predictors were a personality marked by vulnerability to stress (Perceived Stress Scale: R 2, 0.54; β=0.7±0.1; t=7.8; P <0.001) and 1 marked by negativity/social inhibition (Type D Personality Scale: R 2, 0.47; β=0.7±0.1; t=6.7; P <0.001). Suicidal ideation was reported by 16 of 78 (20%) and was predicted by personality traits (Perceived Stress Scale score: R 2, 0.35; odds ratio, 1.22±0.06; P <0.001; Type D Personality Scale score: R 2, 0.48; odds ratio, 1.43±0.14; P <0.001). Effective AF ablation (median AF burden 1% [0–1%] over 12 months) was associated with significant reductions in distress (Hospital Anxiety and Depression Scale score, 13.9±1.8 to 4.3±1.8; P <0.05) and prevalence of suicidal ideation (30–5%; P =0.02). Conclusions: There was a high prevalence of severe psychological distress (35%) and of suicidal ideation (20%) in a tertiary AF population, with personality traits predicting both. Effective AF ablation was associated with significant improvements, suggesting AF itself may be a treatable causative factor of distress.